Clinical application of adult stem cells for therapy for cardiac disease - Ghodsizad, Ali; Ruhparwar, Arjang; Bordel, Viktor; Mirsaidighazi, Ebrahim; Klein, Hans Michael; Koerner, Michael M.; Karck, Matthias; El‐Banayosy, Aly (Cardiovascular therapeutics, 2013)
Introduction Cardiovascular disease is a major cause of death worldwide. Different medical and surgical therapeutic options are well established, but a significant number of patients are not amenable to standard therapeutic options. Cell-based therapies after clinical application have shown different results in recent years. Here, we are giving a comprehensive overview on major available clinical data regarding cell therapy. Background Cell-based therapies and tissue engineering provide new promising platforms to develop upcoming therapeutic options. Initial clinical trials were able to generate promising results. A variety of different stem cell types have been used for the clinical application. Different adult cardiac stem cells and progenitor cells, including mesenchymal, CD34+ and CD133+ autologous human bone marrow-derived stem cells (BMCs), human myoblasts, and peripheral blood-derived stem and progenitor cells (PBSCs) have been used for the therapy for end-stage heart failure. Future experiments will show the importance of novel cell populations and clarify the mechanism causing cell therapy-mediated observed effects. Conclusion Several clinical trials have reported on sole therapy, as well as combined application of autologous adult stem cells with conventional revascularization. The reported promising findings encourage further research in the field of the translational research.
Gesehen am 04.02.2020